On the friction stir welding, tool design optimization, and strain rate-dependent mechanical properties of HDPE–ceramic composite joints. (March 2018) - Raza, Kabeer; Shamir, Muhammad; Qureshi, Muhammad Kashan Akhtar; Shaikh, Abdul Shaafi; Zain-ul-abdein, Muhammad
Friction stir welding is a recently developed technique for joining low-melting metals and polymers. In the present work, friction stir welded joints of high-density polyethylene (HDPE) sheets were produced using a newly designed tool with a concave shoulder and a grooved conical pin. The joints were produced with and without the additions of ceramic particulates including silicon carbide (SiC), alumina, graphite, and silica. The effect of strain rate on the tensile properties of base material and plain welded joints was examined. In addition to tensile properties of composite joints, hardness profiles across the weld nugget were analyzed. It was observed that the increasing strain rate improved both the tensile strength and the ductility of the plain welded joints. The tool was able to yield a joint efficiency of around 84% in the plain welded samples. Although, in terms of joint efficiency, the composite joints were less efficient than the plain welded HDPE, SiC additions were found to yield better material properties relative to other reinforcements. Finally, it was concluded that an SiC–HDPE composite joint can be of practical importance in high strain rate applications, provided the optimum tool design and stir welding parameters are available.